Virtual Trainer for Physical Activities using a Natural User Interface - Jofré Pasinetti, Nicolás (2017)
Despite the known health benefits of regular participation in physical activity people still refuse this practise. Nowadays, Virtual Reality (VR) is a very powerful and compelling computer tool by which humans can interface and interact with computer-generated environments. In this paper, we propose a virtual training system which can be customized for the physical activity level of the user. System provides real time visual action guide and a performance’s feedback of users through a Natural User Interface (NUI). We conduct a brief pilot study to evaluate our virtual trainers in which participants’ performance doing physical activities is evaluated via our NUI. Initial results indicate that virtual training through a NUI is motivating and entertaining for any kind of user, in particular for individuals with low level of physical activity.